APPLICATION SALES HDM BATIK COMPANY USING MICROSOFT VISUAL BASIC 6.0 - Hilman Hilman; Syahril, SKom. Syahril, SKom. (Jurnal Sistem Informasi, 2006)
Scientific writing contains a simple program of computerization penjulan batik, using penginputan goods through production and sales process, which will then be automatically saved in a database and will exit the output display will be received by the customer or buyer as an invoice or receipt and view report required by the batik entrepreneurs. Scientific writing is supported by Visual Basic Programming Language Version 6.0 through the sales process and penginputan makes computerized data processing becomes more efficient and accurate and can provide inventory information available.